In vitro evaluation of the biological performance of macro/ micro-porous silk fibroin and silk-nano calcium phosphate scaffolds - Yan, L.-P. (2016)
This study evaluates the biological performance of salt-leached macro/microporous silk scaffolds (S16) and silk-nano calcium phosphate scaffolds (SC16), both deriving from a 16 wt % aqueous SF solution. Enzymatic degradation results showed that the silk-based scaffolds presented desirable biostability, and the incorporation of calcium phosphate further improved the scaffolds' biostability. Human adipose tissue derived stromal cells (hASCs) were cultured onto the scaffolds in vitro. The Alamar blue assay and DNA content revealed that both scaffolds were non-cytotoxic and can support the viability and proliferation of the hASCs. Scanning electron microscopy observation demonstrated that the microporous structure was beneficial for the cell adhesion while the macroporous structure favored the cell migration and proliferation. The histological analysis displayed abundant extracellular matrix formed inside the scaffolds, leading to the significant increase of scaffolds' modulus. These results revealed that S16 and SC16 could be promising alternatives for cartilage and bone tissue engineering scaffolding applications, respectively.